PENGARUH KOMPETENSI DAN SEMANGAT KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR CAMAT TOMA KABUPATEN NIAS SELATAN - Faerni Lase (Jurnal Ilmiah Mahasiswa Nias Selatan, 2026)
This research aims to determine the influence of competency and work enthusiasm on employee performance at the Toma sub-district office, South Nias Regency. The type of research the author uses is quantitative research. The type of data used is quantitative data and the data source was obtained by distributing questionnaires to employees of the Toma District Head Office. The population in this study was all employees at the Toma Subdistrict Office, totaling 30 people. The sampling technique used non-profitability sampling with a saturated sampling technique, and a sample of 30 people. The data analysis technique used in this research is multiple linear regression analysis. The results of this research show that partially, competency has a significant effect on employee performance and work morale has a significant effect on employee performance. Simultaneously, competency and work enthusiasm have a significant effect on employee performance at the Toma Subdistrict Office, South Nias Regency. Based on the research results and data analysis from this research, the researcher concluded that there is a significant influence of competence and work enthusiasm on employee performance at the Toma Subdistrict Office, South Nias Regency. The suggestions for this research are, 1) it is necessary to increase the competency skills of employees at the Toma Subdistrict Office, South Nias Regency. 2) It is necessary to hold training activities for officials to improve their skills in accordance with their duties in their field. 3) It is necessary to give awards in the form of praise to employees for their achievements and performance. 4) Increase cooperation in carrying out work between employees and leaders. 5) There needs to be awareness in changing the work environment for the better.